The Effect of Methyl Jasmonate on Massoia Lactone Production in Callus Culture of the Endangered Masoyi Plant (Cryptocarya massoy (Oken) Kosterm.) - Aulia, Annisa; Noli, Zozy Aneloi; Idris, Muhammad (HAYATI Journal of Biosciences, 2026)
Cryptocarya massoy (Oken) Kosterm is a plant known for producing essential oils with many applications. However, overexploitation has threatened the sustainability of this plant. This study aims to identify the effect of adding methyl jasmonate to the culture medium on producing secondary metabolites through the callus culture of C. massoy. The methods in this study include callus induction, callus elicitation in liquid culture, callus extraction, analysis of secondary metabolite compounds in C. massoy callus culture, and data analysis. The results show a significant decrease in fresh weight of callus exposed to MeJA stress, depending on the concentration. Regarding secondary metabolites, massoia lactone, the primary compound in C. massoy, was not detected. It is possible that the duration of elicitation was insufficient to induce the biosynthesis and accumulation of detectable levels of massoia lactone. Secondary metabolite production often follows a specific temporal pattern, and certain compounds may require longer exposure times to reach detectable concentrations. The concentration of MeJA influenced the level of other target compound production, where at 0.5 mM MeJA increased the percentage of humulene by 24.64%. MeJA at 1.5 mM enhanced the percentage of ß-copaene (413.11%), ß-ylangene (100%). MeJA at 2 mM increased benzyl benzoate (9.61%). MeJA at 2.5 mM increased α-ylangene (31.25%) and caryophyllene (22.83%). Each MeJA concentration activated specific biosynthesis pathways, influencing the types of secondary metabolites produced. The metabolite screening revealed a predominance of terpenoids, especially sesquiterpenes, which play a role in plant defense.